The novel interactions of Necator americanus with the innate immune system and The development of a 3D immunocompetent model of human skin - Hassan, Asha (2018)
Background: Necatoriasis is a neglected tropical disease caused by the insidious parasite Necator americanus. This hookworm infects and reinfects approximately 500 million individuals worldwide, with a further 5.1 billion at high risk for acquiring the infection. Despite the high level of reinfection, no lasting immunological memory develops in the host. Albeit the profound health implications, chronicity and public health burden in developing countries, many aspects of human Necator americanus infection, particularly early events at the interface with the host immune system, are under researched. These figures and facts highlight the need for new research elucidating the molecular interactions between Necator americanus and the innate immune system. This will aid in the rational design of innovative and more efficient intervention strategies against hookworm infection, which is an essential measure for disease prevention. Objectives: In the context of Necatoriasis, this thesis studied the physical interaction between infective Necator americanus larvae (L3) with human dendritic cells (DCs) and epidermal keratinocytes, investigating the biological consequences. In addition, the development of a platform consisting of human keratinocytes, fibroblast and DCs on a 3D scaffold was constructed as an in vitro model of human skin. Results: The present thesis provides new insights into early immunological events at the interface of DCs and Necator americanus larvae and could explain how L3 affect immunity upon initial interaction with antigen presenting cells. For the first time, the data presented illustrates the sequestration of human DCs onto the sheath of L3 infective Necator americanus larvae, triggering the hookworm to exsheath. Intriguingly, the exposed cuticle of the larvae had negligible interaction with the free DCs. The findings also illustrate that the interaction between DCs and the larvae is mediated via a mandatory interaction with C-type lectin receptors, dendritic cell-specific intercellular adhesion molecule-3 grabbing non-integrin (DC-SIGN) and mannose receptor (MR). Blocking of either receptors with antibodies resulted in an inhibition of DC sequestration and aggregate formation. This demonstrates the biological relevance of previously identified lectin binding molecules on the Necator americanus larvae (L3) sheath in the context of interacting with DCs. These findings allude to a disparity between the surface chemistry of the sheath and larvae that could explain their differential ability to interact with DCs. While the exact nature of differences in the surface properties of the larvae and sheath are yet to be characterised, this data clearly indicates the presence of distinct chemical signatures on the cuticle sheath that attract DCs. However, this not only induces exsheathing but also enables larvae migration without being recognised or challenged by antigen presenting cells. A potential escape mechanism through which the larvae could bypass the immune cells, creating a possible site of ‘temporary immune privilege’. DCs incubated with viable axenic larvae exhibited an immature phenotype as evidenced by the low expression of the maturation markers CD80, CD83, CD86, CD40, and HLA-DR. Subsequently, the ability of DCs to acquire a mature phenotype in response to co-stimulation with lipopolysaccharide (LPS) in the presence of Necator americanus was assessed. These data show that DCs treated with the larvae will remain responsive to LPS stimulation. Additionally while the axenised larvae do not induce any cytokine production by DCs, they seem to suppress LPS induced cytokine expression, however these changes were not statistically significant (p value ≤0.3). Furthermore, the cell-free culture media from DCs, matured in the presence of LPS, had no visible effects on the larvae. Intriguingly, matured DCs in LPS-free culture media render the larvae non-viable through a lysing mechanism, alluding to a modified paracrine signalling response by mature immune cells in culture with the parasite. Interestingly, in the presence of epidermal keratinocytes, ex-sheathing was not mandatory to enable larval burrowing. In fact, only a small number of the larvae sheaths were recoverable from the apical surface of the keratinocyte layer; indicating preferential ensheathed larval burrowing. The data also illustrated the novel behavioural strategies promoting host invasion by Necator americanus larvae, in the presence of epidermal keratinocytes. Larvae were notably slower to exsheath in culture with keratinocytes and exhibited no vigorous movements as observed in DC cultures. This was thought to prevent early exsheathing, as the advantage of larvae maintaining their sheath during the initial stages of infection is in theory highly beneficial.